2020
DOI: 10.4018/978-1-7998-2261-5.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Working With Deaf and Hard-of-Hearing Children From Linguistically Diverse Backgrounds

Abstract: An increasing number of deaf and hard-of-hearing (D/HH) children live in homes where languages other than English or American Sign Language (ASL) are used. This chapter reviews issues of culture and linguistic diversity when working with D/HH multilingual learners (DMLs) from identification and early intervention through school entry. The authors will provide two case studies to explore the issues of service delivery to DMLs and their families: 1) Ji-Hun, who appears to use several spoken languages, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…While highlighted that family involvement in the communication intervention process accounts for the greatest variance in language outcome scores of children with hearing impairment, Scarinci et al (2018) and Garrido-Nag and McCann (2020) detailed the following factors as influential in family involvement:…”
Section: Communication Therapeutic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…While highlighted that family involvement in the communication intervention process accounts for the greatest variance in language outcome scores of children with hearing impairment, Scarinci et al (2018) and Garrido-Nag and McCann (2020) detailed the following factors as influential in family involvement:…”
Section: Communication Therapeutic Approachesmentioning
confidence: 99%
“…Another challenging factor in the choice of communication adopted within the South African context is the challenge created by linguistic and cultural issues that face communication interventionists, with language having a direct implication on service delivery from diagnosis to intervention (Estabrooks, Maclver-Lux & Rhoades 2016;Garrido-Nag & McCann 2020;). The language used in the home, based on whether one or both parents are Deaf, may influence the decision of the communication intervention approach (Scarinci et al 2018).…”
Section: Factors Influencing the Choice Of Communication Therapeutic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenging factor in the choice of communication adopted within the South African context is the challenge created by linguistic and cultural issues that face communication interventionists, with language having a direct implication on service delivery from diagnosis to intervention (Estabrooks, Maclver-Lux & Rhoades 2016;Garrido-Nag & McCann 2020;). The language used in the home, based on whether one or both parents are Deaf, may influence the decision of the communication intervention approach (Scarinci et al 2018).…”
Section: Factors Influencing the Choice Of Communication Therapeutic ...mentioning
confidence: 99%
“…Language delay [ 23 25 ] thought to be associated with language deprivation [ 26 , 27 ] can in turn lead to delays in Theory of Mind (ToM) (empathy-related) skills [ 14 ]. For example, research has shown deaf toddlers exchanging fewer social-communicative signals and having more difficulties understanding the intentions of others [ 28 ].…”
Section: Introductionmentioning
confidence: 99%